2016
DOI: 10.1590/2446-4740.02315
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between spectral and temporal mechanomyography features during functional electrical stimulation

Abstract: Introduction: Signal analysis involves time and/or frequency domains, and correlations are described in the literature for voluntary contractions. However, there are few studies about those correlations using mechanomyography (MMG) response during functional electrical stimulation (FES) elicited contractions in spinal cord injured subjects. This study aimed to determine the correlation between spectral and temporal MMG features during FES application to healthy (HV) and spinal cord injured volunteers (SCIV). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In applications with comparisons between the MMG signal and the force response the biceps brachii (Orizio et al, 1989) and rectus femoris (Krueger et al, 2016;Shin et al, 2016) are the muscles more used due its easy accessibility and comparison capability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In applications with comparisons between the MMG signal and the force response the biceps brachii (Orizio et al, 1989) and rectus femoris (Krueger et al, 2016;Shin et al, 2016) are the muscles more used due its easy accessibility and comparison capability.…”
Section: Introductionmentioning
confidence: 99%
“…However, those researchers did not show if there is a trend related to different force levels or if this influence occurs in all (three) accelerometers axes. With the force increase, new motor units located in different places of the muscle are recruited influencing the vibration pattern of each axis (Herda et al, 2010) once the amplitude of MMG for the rectus femoris muscle contraction represents a mechanical 3-axis signal (Shin et al, 2016) and it is generated by the motor units coherence increasing the mechanical wave amplitude (Krueger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Four studies [ 58 61 ] have been identified to discuss the physiological behaviors after fatigue administration. In one of these studies [ 58 ], the authors evaluated the correlation between the temporal and spectral features of MMG from 10 SCI and 10 health volunteers undergoing recovery by NMES. and from the analysis of window length were examined.…”
Section: Analysis and Discussion Of Mmg And Nmesmentioning
confidence: 99%
“…Mechanomyography (MMG) is a noninvasive technique that can be also used for monitoring muscle biofeedback as, for instance, can be apply in the control of myoelectrical [1][2][3] and neural prostheses [4] and to support physical therapy sessions [5,6]. The MMG records vibrations [7] of detectable muscle fibers on the surface of the skin.…”
Section: Introductionmentioning
confidence: 99%